Thermally triggered polyrotaxane translational motion helps proton transfer - Xiaolin Ge (Nature Portfolio, 2018)
Proton exchange is critical in many applications, such as in conductive proton exchange membranes, but achieving fast proton exchange still remains a challenge. Here the authors report fast proton exchange in a rotaxane based polymer by exploiting thermally triggered translational motion of the mechanically bonded rotaxane.